INFORMATION SYSTEM OF TUITION AND THESIS PAYMENT VERIFICATION WITH ADAPTIVE LAYOUT DESIGN - Bambang Adiwinoto; Yohanes Setiawan Japriadi; Lukas Tommy (Jurnal Techno Nusa Mandiri, 2020)
The verification system of tuition and thesis payment at ISB Atma Luhur which is running is felt to be less effective and efficient because students must come directly to campus with proof of payment during working hours to verify the payment. Also, there is the possibility of negligence by the finance department that only stamped the payment slip without doing a flag, consequently, related students were unable to carry out the selection of lecture groups and thesis supervisors when the schedule began. This caused them to not get the favorite lecture groups and thesis supervisors because the quota had run out. To overcome this problem, an information system for verification of tuition payment and web-based thesis verification will be developed with an adaptive layout design so that it can be accessed by laptop or smartphone users without reducing comfort during operation. The system development model and tool used in this research are the waterfall model and the Unified Modeling Language (UML), respectively. The developed system can be used by students to upload proof of payment and monitor the verification status of proof of payment that was previously uploaded. The system can also be used by the finance department to verify payments, as well as display and print payment verification reports. The developed system can be accessed anywhere and anytime so that the efficiency and effectiveness of the verification process are increased.